A CASE-CONTROL STUDY OF HEMATOLOGICAL ANALYSIS ON DIABETES AND COVID-19 SEVERITY - Ahmad Ghiffari; Hartanti, Miranti; Ivanka, Agnes; Permana, Adhi (Fakultas Kedokteran Universitas Sriwijaya, 2024)
This study investigates the relationship between diabetes comorbidity and COVID-19 severity in Muhammadiyah Palembang Hospital, focusing on hematological parameters as potential predictors of disease progression. Utilizing a case-control design with 61 respondents, demographic data, COVID-19 severity classifications, and hematological profiles were analyzed. Results reveal a prevalence rate of diabetes mellitus among COVID-19 patients at 32.8%, with diabetic individuals experiencing higher rates of moderate clinical complications. Hematological analysis demonstrates variations in parameters such as hemoglobin levels, platelet counts, and neutrophil-to-lymphocyte ratio between diabetic and non-diabetic COVID-19 patients. These findings underscore the importance of tailored interventions for diabetic individuals infected with COVID-19 and highlight the potential of hematological parameters in predicting disease severity. The study suggests the need for larger-scale, multicenter research to validate findings and inform evidence-based clinical practice in managing COVID-19 patients with comorbid diabetes mellitus.